Phylogenetic reconstruction and evolution of the Rab GTPase gene family in Amoebozoa - Porfírio-Sousa, Alfredo L; Tice, Alexander K; Brown, Matthew W; J G Lahr, Daniel (Small GTPases, 2022)
Rab GTPase is a paralog-rich gene family that controls the maintenance of the eukaryotic cell compartmentalization system. Diverse eukaryotes have varying numbers of Rab paralogs. Currently, little is known about the evolutionary pattern of Rab GTPase in most major eukaryotic 'supergroups'. Here, we present a comprehensive phylogenetic reconstruction of the Rab GTPase gene family in the eukaryotic 'supergroup' Amoebozoa, a diverse lineage represented by unicellular and multicellular organisms. We demonstrate that Amoebozoa conserved 20 of the 23 ancestral Rab GTPases predicted to be present in the last eukaryotic common ancestor and massively expanded several 'novel' in-paralogs. Due to these 'novel' in-paralogs, the Rab family composition dramatically varies between the members of Amoebozoa; as a consequence, 'supergroup'-based studies may significantly change our current understanding of the evolution and diversity of this gene family. The high diversity of the Rab GTPase gene family in Amoebozoa makes this 'supergroup' a key lineage to study and advance our knowledge of the evolution of Rab in Eukaryotes.
Keywords: eukaryotic evolution; Phylogeny; Rab therapeutic intervention; Amoebozoa; fylogeneze; rab GTP-Binding Proteins; Rab proteiny vázající GTP; Evolution, Molecular; molekulární evoluce; cellular biology; Phylogenomics; Eukaryota